Penerapan Restorative Justice Terhadap Tindak Pidana Pencemaran Nama Baik Pada Laman Whatsapp di Kampung Tebaci Jakarta Barat - Vanya Ayu Andini; Agus Ariadi (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2026)
This research is motivated by the rampant defamation in cyberspace along with the massive use of Whatsapp, especially in Kampung Tebaci, West Jakarta. The purpose of this study is to analyze regulations and identify obstacles and challenges in the implementation of Restorative Justice to defamation cases through Whatsapp in Tebaci Village. The research method used is empirical juridical with a sociological juridical approach, through in-depth interviews and literature studies. The legal basis used in the implementation of Restorative Justice includes the provisions of the new Criminal Code, the new ITE Law, Police Regulation Number 8 of 2021, and the Constitutional Court Decision Number 105/PUU-XXII/2024. The findings of this study show that the Restorative Justice approach is more suitable to be applied to complaints based on social relations because the main goal is not punishment, but the restoration of social relations that focuses on dialogue, mediation, and peace. In its implementation, it involves the Neighborhood Unit, Neighborhood Unit, National Police Headquarters, TNI Binmas, perpetrators, victims, families of perpetrators and victims until a peace agreement is reached. Meanwhile, the implementation of Restorative Justice in Tebaci Village still experiences obstacles and challenges, such as the egos of the disputing parties, dense settlement conditions, and the absence of technical guidelines for penal mediation in densely populated areas. Therefore, specific regulations, digital conflict mediation training for community institutions in Tebaci Village are needed, and improving people's digital literacy.